WORKSHOP JARINGAN LISTRIK DAN PEMBUATAN PENERANGAN JALAN UMUM DI LUMAJANG - Hartono Hartono; Rifdian I.S.; Kustori Kustori; Slamet Hariyadi; Suhanto Suhanto; Fiqqih Faizah; Siti Julaihah (Journal of Public Transportation Community)
Abstract Public street lighting is one of the need of today’s society. Every street in residential areas always requires public street lighting. This is because every community activity that takes place outside the home, especially at night definity requires proper lighting. Street lighting is closely related to public safety and security. Community Service Activities (PKM) are condused to address environmental issues. One solution to these problems is to organize a Workshop on electricity netwroks and public street lighting on the slopes of Mount Semeru in Lumajang. The results of this activity, revealed that the provision of PJU lights assisted the community sevice project was titled "Electrical Network Workshop and the Insatallation of Public Street Lighting in Lumajang". This program is implemented by a lecturer at the Surabaya Aviation Polytechnic to appply electrical engineering knowledge and provide benefits to the community by improving street lighting Keywords: Elecric Network, Public Street Lighting, Safety